Depicting Science in a Public Debate: The Philippine Legal Challenge Against GMO Eggplant - Ponce de Leon, Inez Z (Archīum Ateneo, 2019)
In 2015, the Philippine Supreme Court ruled against the field testing of Bt eggplant, a genetically modified crop. This decision was covered extensively in the local press, forcing scientists to defend their research. We used qualitative, inductive analysis to examine how three news outlets constructed science in their coverage of the issue. We found that science was constructed through four themes: science searched for proof, absolute consensus had to be reached, the characteristics of scientific inquiry are used to discredit scientists, and science is aware of its logical limits. These findings have implications for the public acceptance of innovations.